2015
DOI: 10.1021/acs.jpca.5b06565
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Re-examination of the Criegee Intermediate–Sulfur Dioxide Reaction

Abstract: The atmospheric oxidation of sulfur dioxide by the parent and dimethyl Criegee intermediates (CIs) may be an important source of sulfuric acid aerosol, which has a large impact on radiative forcing and therefore upon climate. A number of computational studies have considered how the CH2OOS(O)O heteroozonide (HOZ) adduct formed in the CI + SO2 reaction converts SO2 to SO3. In this work we use the CBS-QB3 quantum chemical method along with equation-of-motion spin-flip CCSD(dT) and MCG3 theories to reveal new det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
108
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(129 citation statements)
references
References 115 publications
20
108
1
Order By: Relevance
“…The rate constants from the reactions of sCI + H 2 O and sCI + (H 2 O) 2 range from 1.0 × 10 −14 to 2.0 × 10 −19 cm 3 molecule −1 s −1 and 1.6 × 10 −11 to 2.6 × 10 −14 cm 3 molecule −1 s −1 , respectively (Table ). The rate coefficients range between (2.0–7.0) × 10 −12 cm 3 molecule −1 s −1 for sCI + NO 2 reaction , , , , (2.4–22.0) × 10 −11 cm 3 molecule −1 s −1 for sCI + SO 2 reaction , and (1.0–6.0) × 10 −10 cm 3 molecule −1 s −1 for sCI + carboxylic acid reaction .trueright sCI Products trueright sCI +H2normalO Products trueright sCI +(H2normalO)2 Products trueright sCI + NO 2 NO 3+ carbonyl trueright sCI + SO 2 SO 3+ carbonyl trueright sCI + RCOOH Products …”
Section: Introductionmentioning
confidence: 99%
“…The rate constants from the reactions of sCI + H 2 O and sCI + (H 2 O) 2 range from 1.0 × 10 −14 to 2.0 × 10 −19 cm 3 molecule −1 s −1 and 1.6 × 10 −11 to 2.6 × 10 −14 cm 3 molecule −1 s −1 , respectively (Table ). The rate coefficients range between (2.0–7.0) × 10 −12 cm 3 molecule −1 s −1 for sCI + NO 2 reaction , , , , (2.4–22.0) × 10 −11 cm 3 molecule −1 s −1 for sCI + SO 2 reaction , and (1.0–6.0) × 10 −10 cm 3 molecule −1 s −1 for sCI + carboxylic acid reaction .trueright sCI Products trueright sCI +H2normalO Products trueright sCI +(H2normalO)2 Products trueright sCI + NO 2 NO 3+ carbonyl trueright sCI + SO 2 SO 3+ carbonyl trueright sCI + RCOOH Products …”
Section: Introductionmentioning
confidence: 99%
“…Please do not adjust margins Please do not adjust margins (3.9 ± 0.7) × 10 -11 ξ (3.80 ± 0.04) × 10 -11 ξ (3.42 ± 0.42) × 10 -11 ϒ (4.1 ± 0.3) × 10 -11 ξ (3.53 ± 0.29) × 10 -11 ϒ (3.3 ± 0.9) × 10 -11 ϒ 4.0 × 10 -10 (3.68 ± 0.02) × 10 -11 298 298 298 293 295 295 295 295 ± 2 Kurtén et al 68 Kuwata et al 69 Welz et al 56 Chhantyal-Pun et al 21 Stone et al 57 Sheps 24 Liu et al 23 Berndt et al 70…”
mentioning
confidence: 98%
“…If, as suggested by , the secondary ozonide (SOZ) formed from the reaction between larger SCI and SO 2 can stabilize and undergo bimolecular reaction without formation of SO 3 , the difference in the rate coefficients for the different experiments could be partly explained. However, more recent theoretical work (Kuwata et al, 2015) found additional low-lying pathways that make collisional stabilization of the SOZ unlikely. Experiments by Carlsson et al (2012) and Ahrens et al (2014) observed high yields of SO 3 close to unity suggesting that the SOZ is not lost under the conditions used, i.e.…”
Section: Missing H 2 So 4 Oxidantmentioning
confidence: 99%